Ex-ante determinants of IPOs: A dataset for the Malaysian IPOsMendeley Data - Ali Albada; Soo-Wah Low; Rabie A. Ramadan; Khalid Al Qatiti; Muataz Salam Al-Daweri (Data in Brief, 2025)
This article introduces a comprehensive dataset for investigating the ex-ante determinants of Initial Public Offerings (IPOs) first-day initial returns, investor demand, and the information gap experienced by investors for listed firms on Bursa Malaysia over the period 2004–2021. The final sample comprises 350 IPOs priced using the fixed-price method, which were hand-collected from multiple sources. The data in this dataset plays an important role in providing insightful decision-making tips for prospective investors operating in an environment characterized by high information asymmetry. Furthermore, the dataset opens avenues for future research, such as cross-country studies exploring the impact of country-specific factors on IPO initial return outcomes.